On the Advanced Mechanical Properties of Fe–Cu and Y–Cu Nanocomposites Obtained by Mechanical Alloying - Dashevskyi, M.; Belyavina, N.; Nakonechna, O.; Melnichenko, M.; Revo, S. (Металлофизика и новейшие технологии, 2018)
In this study, the Fe–Cu and Y–Cu nanocomposites are synthesized by mechanical alloying of the elemental powder mixture of the iron, copper and crushed yttrium particles in a high-energy planetary ball mill inside the argon atmosphere. Phase transformations in obtained composite materials are studied by X-ray powder-diffraction methods. The metastable supersaturated α-(Fe, Cu) solid solution is formed in the Fe–Cu nanocomposites during milling process, while the phase transformation during milling of the equiatomic Y–Cu mixture follows the reaction: Y + Cu → YCu + YCu₂. All obtained materials demonstrate improved mechanical properties. A set of measurements of the mechanical characteristics is carried out. The hardness measured for both FeCu and YCu nanocomposites is higher than that for conventional bulk alloys due to the grains’ refinement during milling process. Besides, the synthesized nanocomposites are characterized by relatively low values of the Young’s modulus.